A Model for the Formation of Niobium Structures by anodization - Bianchin, Ana Carolina Viero (2018)
The fluoride use for anodizing electrolytes has been primarily responsible for the formation of nanoporous oxides at valve metals, except aluminum, since it causes a dissolution process. This study presents the formation of an oxide model according to the following anodizing parameters: 100 V, 12.73 mA/cm², room temperature and the niobium samples anodized in niobium oxalate and oxalic acid electrolytes without and with the addition of HF for 5, 30 and 60 min. The anodized samples were analyzed morphologically by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), atomic force microscopy (AFM) and the hydrophobicity of the samples was assessed by the sessile drop method. The presence of fluor in the niobium oxalate electrolyte formed oxides with lower a dissolution and a low hydrophobicity compared to the one formed in oxalic acid was attributed to the incorporation of niobium and oxalate ions. Thereby, the model proposed in this paper showed that during anodization the migration of the fluoride ion into the oxide occurs at high speed, which results in the formation of microcones, leading to the formation of discrete layers of porous oxide.